1954
DOI: 10.1039/jr9540004616
|View full text |Cite
|
Sign up to set email alerts
|

Mixed liquid crystals

Abstract: A number of binary systems have been investigated in which one component can form a nematic liquid-crystal phase and the other not. In all cases studied the liquid phase is apparently a homogeneous single phase which may or may not be anisotropic. There was no indication that two distinct liquid phases, one isotropic and the other anisotropic, could coexist over a range of temperature, for a binary mixture of a given composition. Thermodynamic arguments show, however, that such a situation is impossible for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1971
1971
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…This shift reveals the presence of a normally monotropic mesophase on heating. Similar work with impurities and two-component systems has been reported in detail by Dave et al [13,21,22] for nematic-mesophase-forming materials. The van Schuppen palmitate ester behavior can best be explained by a selective impurity rather than by separate crystal forms of the solid.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This shift reveals the presence of a normally monotropic mesophase on heating. Similar work with impurities and two-component systems has been reported in detail by Dave et al [13,21,22] for nematic-mesophase-forming materials. The van Schuppen palmitate ester behavior can best be explained by a selective impurity rather than by separate crystal forms of the solid.…”
Section: Discussionsupporting
confidence: 82%
“…Preliminary evidence indicates that the solid-phase polymorphy of the cholesteryl esters may be at least as complex as the mesophase polymorphy. In part this apparent polymorphy may be due to selective impurities previously reported for nematic systems [13].…”
Section: Introductionmentioning
confidence: 66%
“…24,35 Early work on the effect of solvents on the properties of nematic LCs reported a linear decrease at low solvent content. 27 Doping with non-nematogenic solvent species was later proposed as a method to bi-directionally tune T I-N within a limited temperature range: lowering T I-N by dilution as well as increasing T I-N through donor-acceptor interactions of nematic mesogens and solvent molecules. 36 More recently, a number of studies have investigated the effect of non-mesogenic impurities on the phase behaviour of 4-cyano-4 0 -octylbiphenyl (8CB).…”
Section: Resultsmentioning
confidence: 99%
“…[20][21][22][23][24][25][26] Early work focused on elucidating the effect of non-nematogenic doping on the isotropic-to-nematic phase transition temperature T I-N . 27 The phase behaviour of binary mixtures of low molecular weight nematic LCs and nonnematogenic species is typically well described by hybrid mean field models that take into account aspects of the Maier-Saupe as well as the Flory-Huggins theory. [28][29][30][31][32] For a binary liquid mixture of a nematic LC and an isotropic liquid, the consideration of nematohydrodynamics enables to predict the kinetic effects of the phase separation.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the applications of liquid crystal solutions are (1) the fabrication of coloured liquid crystal displays by doping dyes in liquid crystal media [l-31, (2) the creation of new chiral smectic C (S:) materials by dissolving chiral dopants in S,. hosts [4], (3) the use of liquid crystals as an anisotropic solvent for the studies of molecular geometry and chemical shift anisotropy of solute molecules [5-141, and (4) measurement of order parameters of the host by using the solute as a 'probe' [15-181. The early work by Dave and Dewar showed that the addition of non-mesomorphic compounds to a nematic liquid crystal results in a depression of both the melting point and the nematic-isotropic transition point TNI, and the disturbing effect of the solute to its host increases with the molecular size of the solute [19]. Because of difficulties in studying the nematic solvent phase itself, the perturbation of various solutes on the orientational ordering of the host has often been estimated by observing properties of the solute, including the use of special 'probe' molecules.…”
Section: Introductionmentioning
confidence: 99%